2017
DOI: 10.1016/j.trf.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Are situation awareness and decision-making in driving totally conscious processes? Results of a hazard prediction task

Abstract: Detecting danger in the driving environment is an indispensable task to guarantee safety which depends on the driver's ability to predict upcoming hazards. But does correct prediction lead to an appropriate response? This study advances hazard perception research by investigating the link between successful prediction and response selection. Three groups of drivers (learners, novices and experienced drivers) were recruited, with novice and experienced drivers further split into offender and non-offender groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 36 publications
3
15
0
Order By: Relevance
“…Operators' knowledge of the components and their interrelationships may be organised on different levels of detail, called Blattices^, and Moray (1990) suggests that at certain levels, these lattices may differ considerably from the actual system and may even constitute wrong knowledge. In a recent study by Gugliotta et al (2017), drivers are shown video clips ending with a hazardous situation. Drivers are more accurate in answering a question asking what they would do in a similar situation, than they are in answering a question on their awareness of what the hazard is, where it is located and what happens next.…”
Section: Implicit Learning and Retrievalmentioning
confidence: 99%
“…Operators' knowledge of the components and their interrelationships may be organised on different levels of detail, called Blattices^, and Moray (1990) suggests that at certain levels, these lattices may differ considerably from the actual system and may even constitute wrong knowledge. In a recent study by Gugliotta et al (2017), drivers are shown video clips ending with a hazardous situation. Drivers are more accurate in answering a question asking what they would do in a similar situation, than they are in answering a question on their awareness of what the hazard is, where it is located and what happens next.…”
Section: Implicit Learning and Retrievalmentioning
confidence: 99%
“…On the other hand, risk estimation can be measured with the question: To what extent does the situation you have seen appear dangerous? Respond 1 if it seems slightly dangerous, 6 if it seems highly dangerous [20]. Previous studies have concluded that young drivers are particularly susceptible to "optimism bias", defined by Weinstein (1980) as the tendency to believe that one is more skilled and less likely to experience a negative event than one's peers, and higher perceptions of driving skill are associated with lower perceptions of accident risk.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have concluded that young drivers are particularly susceptible to "optimism bias", defined by Weinstein (1980) as the tendency to believe that one is more skilled and less likely to experience a negative event than one's peers, and higher perceptions of driving skill are associated with lower perceptions of accident risk. [20][21][22][23][24]. found that novice drivers scored significantly lower than experienced drivers when they estimated their driving skills, such as driving ability, awareness of others and self-confidence in driving, although at the same time, they estimated traffic situations as more dangerous.…”
Section: Introductionmentioning
confidence: 99%
“…Within the SA model, there are three levels, namely, perception (level 1), comprehension (level 2), and projection (level 3) [ 21 ], which respectively approximate the source, location, and projection of the road hazard. A number of studies have applied the SA model to hazard prediction assessments and found that it successfully discriminates among driver groups with varying experience [ 19 , 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The three questions are “What is the hazard?” (question 1), “Where is the hazard?” (question 2) and “What happens next?” (question 3). During the experiment, participants are required to select a response from the given choices, or orally respond to questions when a video clip is cut to black or the final still image of the clip remains on the screen [ 10 , 18 , 22 ]. Compared to the reaction time paradigm, the WHN method can prevent the adverse effects of risk threshold and response criterion on participants’ response [ 16 , 25 ].…”
Section: Introductionmentioning
confidence: 99%